INTEGRASI KEILMUAN DAN IMPLIKASI AIK DALAM MEWUJUDKAN INSAN BERKEMAJUAN DI PERGURUAN TINGGI - Busahdiar, Busahdiar; Karimah, Ummah; Idrus, Ali; Taufik, Azhar; Wahyuni, Sri; Akbar, Tubagus Osama; Agustin, Cahya Lestari (FIKRAH, 2023)
The concept of Insan Berkemajuan is found in the Muhammadiyah slogan as a da’wah movement. The perspective of a progressive person is a person who has superior science and technology achievements. People who have prosperous and prosperous conditions. And progressive people can bring people to power, so that the governance of the people and nation can be carried out according to the values of Islamic da’wah. And progressive people are able to invite, teach and realize Islamic values in society. So that a truly Islamic society will be realized. Through educational institutions in higher education to realize students become progressive people, they integrate knowledge on Al Islam and Kemuhammadiyahan (AIK) in every lecture. This research is a qualitative research with interview method. The data collection method in this study uses the documentation method by viewing and recording relevant available reports. The data analysis technique used is content analysis to draw conclusions from the documents used. Based on the results of the researcher’s study of scientific integration in AIK implications for realizing progressive people in every lecture applied by lecturers, namely in the learning process integrated with Islamic teachings, Lecturers explicitly include AIK values in the Syllabus / RPS, Lecturers and Students behave and behave in accordance with Islamic teachings, Lecturers in the lecture process are integrated with Islamic teachings, and internalize Islamic values in each course.